Integrative taxonomic consideration of the Holarctic Euconulus fulvus group of land snails (Gastropoda, Stylommatophora). Issue 2 (17th February 2020) - Horsáková, Veronika; Nekola, Jeffrey C.; Horsák, Michal
Abstract : While among the most common Holarctic land snails, species of the Euconulus fulvus group have been subject to considerable recent taxonomic controversy. Based on 76 Euconulus populations collected across Eurasia and North America, we empirically evaluated these competing taxonomic hypotheses through an integration of nDNA and mtDNA phylogenetics, shell morphometrics and various qualitative traits. Our results support the existence of five taxa: Euconulus alderi (Atlantic Europe to western North America), E. fresti sp. nov. (North America), E. fulvus fulvus (Europe), E. fulvus egenus (central Asia to Atlantic North America), and E. polygyratus (north-eastern North America). Each species-level entity possessed a unique suite of observable shell features allowing for accurate identification without need of DNA sequence information. Our data did not support the recent erection of E. callopisticus, E. praticola, and E. trochiformis to species-level status. This work also helps illustrate the importance of using consensus across DNA and shell/soft body features in assessing species-level taxonomy and in determining those features which allow for accurate identification. It furthermore documents the importance of basing taxonomic work on samples drawn from across the entire geographic and ecological range of the study group. http://zoobank.org/urn:lsid:zoobank.org:pub:97985479-EDF8-4B94-A825-AC42BF31F597